Photosensitizing Properties of Alkynylrhenium(I) Complexes [Re(–C≡C–R)(CO)3(N∩N)] (N∩N = 2, 2′‐bipy, phen) for H2 Production. Issue 19 (4th June 2014) - Oberholzer, Miriam; Probst, Benjamin; Bernasconi, Dominik; Spingler, Bernhard; Alberto, Roger
Abstract: A series of complexes of the type [ fac ‐Re(X)(CO)3 (N∩N)] (X = –C≡C–R, N∩N = 2, 2′‐bipy, 2, 2′‐phen) were synthesized and fully characterized. Their photophysical characteristics make them very convenient photosensitizers (PSs). Upon light irradiation, H2 formation was observed for all alkynyl complexes in the presence of a water‐reducing catalyst (WRC) and a sacrificial electron donor. Relative rates of H2 production indicate a dependency upon the diimine ligands rather than upon the nature of the σ‐bonded alkynyl derivatives. The coordinated acetylene group induces a redshift of the λ max of the MLCT band in UV/Vis spectroscopy as compared to those of the corresponding halides, nitriles, or cationic Re I complexes, such as [ fac ‐ReX(CO)3 (N∩N)] (X = pyridine, H2 O, N∩N = bipy, phen). Abstract : Upon irradiation, luminescent alkynylrhenium(I) complexes [Re(–C≡C–R)(CO)3 (N∩N)] (N∩N = bipy, phen) allow for TONs up to 400 (H/Re) in photocatalytic proton reduction in the presence of a sacrificial electron donor and cobalt‐based water reduction catalyst. The acetylene group induces a redshift in the UV/Vis spectrum, ensuring a more efficient conversion of solar light into chemical energy.